The role of the state in the touristification of Lisbon - Estevens, Ana; Cocola-Gant, Agustín; López-Gay, Antonio; Pavel, Fabiana (Cities, 2023)
The explanation regarding the recent touristification of cities has significantly focused on the ability of platforms such as Airbnb to offer millions of tourist beds in areas that were not planned for tourism use. Exploring Lisbon, we offer instead a political economic explanation where touristification is the result of the active intervention of the neoliberal state. Lisbon moved from a phase of abandonment to be gentrified by tourism in a very short period. To explain this, we examine how the state absorbed the cost of redevelopment, thus ensuring that private capital could extract profits from rehabilitation, and allowed developers to build the most profitable product with no limitations, which to a great extent are short-term rentals, hotels, and luxury housing for transnational users. By examining how the central city has been re-invented to serve the needs of private capital, we develop a dialogue between this general process of gentrification and how it is experienced in Southern Europe as a wave of intense touristification. We contextualize this within the historical political economic process in which the European South has progressively become a space of vacation for transient populations who are presented as the new class to be served. •We estimate the weight of tourism in the rehabilitation of the housing stock in Lisbon.•We offer a political economic explanation of touristification in the context of a broader gentrification process.•We explore how the state absorbed the cost of redevelopment to ensure that private capital extract profits from rehabilitation.•We found that in the historic centre rehabilitations overwhelmingly gave way to hotels and buildings with short-term rentals.